2002
DOI: 10.1128/iai.70.6.3068-3072.2002
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensin 1 Contributes to Pulmonary Innate Immunity in Mice

Abstract: Innate immunity serves as a first line defense in vertebrate organisms by providing an initial barrier to microorganisms and triggering antigen-specific responses. Antimicrobial peptides are thought to be effectors of innate immunity through their antibiotic activity and direct killing of microorganisms. Evidence to support this hypothesis in vertebrates is indirect, based on expression profiles and in vitro assays using purified peptides. Here we investigated the function of antimicrobial peptides in vivo usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(145 citation statements)
references
References 24 publications
4
137
0
4
Order By: Relevance
“…For example, previous studies using surfactant proteins A or D or ␤-defensin knockout mice have demonstrated impaired bacterial clearance from the lung. [27][28][29] In addition, airway epithelial cells produce several other major host defense molecules such as lactotransferrin. 30 The present results of impaired Mp clearance from SPLUNC1 Ϫ/Ϫ mouse lungs advance the lung innate immunity field by demonstrating the in vivo function of SPLUNC1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies using surfactant proteins A or D or ␤-defensin knockout mice have demonstrated impaired bacterial clearance from the lung. [27][28][29] In addition, airway epithelial cells produce several other major host defense molecules such as lactotransferrin. 30 The present results of impaired Mp clearance from SPLUNC1 Ϫ/Ϫ mouse lungs advance the lung innate immunity field by demonstrating the in vivo function of SPLUNC1.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Mice deficient in hBD-1 had delayed clearance of Haemophilus influenzae from the lung. 20 The DEFB1 sequence contains nuclear factor interleukin-6 and interferon-d consensus sites, suggesting that inflammatory markers induce hBD-1 expression. 21 In addition, complex interactions between serpins and defensin suggest that defensins also have a role in regulating inflammatory processes within the airway.…”
Section: Discussionmentioning
confidence: 99%
“…The key role of antimicrobial peptides in mammalian host defense is made evident by mice with disrupted antimicrobial peptide genes that are prone to infection in the affected epithelial organs, including the skin (3)(4)(5). In humans, the role of epithelial antimicrobial peptides in host defense is suggested by studies of two major human skin diseases with a defective skin barrier, atopic dermatitis and psoriasis.…”
Section: Differential Regulation Of ␤-Defensin Expression In Humanmentioning
confidence: 99%